2023
DOI: 10.2147/prbm.s392414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Appearance Anxiety on the Online Impulse Purchases of Fashionable Outfits Among Female College Students During Pandemic Periods: The Mediating Role of Self-Control and the Moderating Role of Subjective Socioeconomic Status

Abstract: Purpose With the rise of social media, an increasing number of young females have focused more attention on their body image, leading to social appearance anxiety. Thus, the current study aimed to investigate a moderated mediation model of social appearance anxiety and online impulse purchases of fashionable outfits through self-control moderated by subjective socioeconomic status during the pandemic. Methods A total of 1651 female college students ( Age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 95 publications
1
12
3
Order By: Relevance
“…Accordingly, the yearly gross income of the sample was typically less than €20,000 (23.34%) and no more than €30,000 (20.89%). Not surprisingly, most respondents were females (78.96%), thus, corroborating previous studies in the fashion industry, which indicated that females tend to be both more inclined to make decisions in apparel shopping (Xiao et al , 2023) and more prone to sustainable consumption than men (Becerra et al , 2023).…”
Section: Methodssupporting
confidence: 87%
“…Accordingly, the yearly gross income of the sample was typically less than €20,000 (23.34%) and no more than €30,000 (20.89%). Not surprisingly, most respondents were females (78.96%), thus, corroborating previous studies in the fashion industry, which indicated that females tend to be both more inclined to make decisions in apparel shopping (Xiao et al , 2023) and more prone to sustainable consumption than men (Becerra et al , 2023).…”
Section: Methodssupporting
confidence: 87%
“…The impact of others' behaviors varies depending on the degree of intimacy in their relationship with the individual. Perceptions of the existing behavior of close others have a substitutive regulatory effect on moral self-regulation, which is known as the "variable moral selfregulation effect" [10]. When individuals have less proximity to others, their behavior exerts a diminished influence on the individual's moral self-regulation.…”
Section: The Effect Of Cognition Of Others' Behavior On Moral Self-re...mentioning
confidence: 99%
“…According to Xiao, Zhan, and Zhong, human moral behavior could be influenced by close others [10]. In their study, the participants were requested to assess a same-sex close acquaintance's engagement in common environmental behavior (recycling waste paper) or uncommon environmental behavior (writing letters to the government with suggestions for environmental protection) [10]. The results indicated that more environmentally friendly behaviors by close others may lead individuals to show a greater degree of self-interest in the subsequent experiment [10].…”
Section: The Effect Of Cognition Of Others' Behavior On Moral Self-re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial research to understand online shopping behavior focused on attitudes toward online shopping and motivations to shop online (Bhatnagar et al, 2000;Kim & Park, 2005;Shim et al, 2001). Recent research has endeavored to understand the online shopping experiences of various consumers like women (Sathya et al, 2023), students (Xiao et al, 2023), young consumers (Tan et al, 2024), senior citizens (Roy et al, 2023) and low-income consumers (Zhang et al, 2023). However, little attention has been paid to the shopping experiences of persons with disabilities (PWD), especially consumers with visual impairment (CWV) (Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%